2014
DOI: 10.1016/j.biopsycho.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy anxiety and prenatal cortisol trajectories

Abstract: Pregnancy anxiety is a potent predictor of adverse birth and infant outcomes. The goal of the current study was to examine one potential mechanism whereby these effects may occur by testing associations between pregnancy anxiety and maternal salivary cortisol on 4 occasions during pregnancy in a sample of 448 women. Higher mean levels of pregnancy anxiety over the course of pregnancy predicted steeper increases in cortisol trajectories compared to lower pregnancy anxiety. Significant differences between cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 45 publications
4
67
0
8
Order By: Relevance
“…Davis and Sandman (2010) recently suggested that this kind of stress is perhaps the best predictor of infant outcome. Moreover, at least three studies reveal that maternal reports of this measure correspond positively with cortisol blood levels in pregnant women, supporting the proposed biological processes thought to underlie the FPH (Kane, Dunkel-Schetter, Glynn, Hobel, & Sandman, 2014;Rini et al, 1999;Wadhwa, Sandman, Porto, Dunkel-Schetter, & Garite, 1993).…”
Section: Stress Measurementioning
confidence: 69%
“…Davis and Sandman (2010) recently suggested that this kind of stress is perhaps the best predictor of infant outcome. Moreover, at least three studies reveal that maternal reports of this measure correspond positively with cortisol blood levels in pregnant women, supporting the proposed biological processes thought to underlie the FPH (Kane, Dunkel-Schetter, Glynn, Hobel, & Sandman, 2014;Rini et al, 1999;Wadhwa, Sandman, Porto, Dunkel-Schetter, & Garite, 1993).…”
Section: Stress Measurementioning
confidence: 69%
“…We cannot exclude the possibility that other markers of cortisol physiology may be more strongly linked to maternal psychological stress/anxiety and hence more relevant for fetal programming processes. For example, in a recent study of Kane et al (2014) the relation between the trajectory of changes in cortisol concentrations during pregnancy were examined in relation with pregnancy anxiety. These authors found that higher mean levels of pregnancy anxiety from mid to late pregnancy was related to steeper increases in cortisol secretion over pregnancy.…”
Section: Maternal Prenatal Cortisol: Mediator Between Prenatal Stressmentioning
confidence: 99%
“…Antepartum anxiety is a risk factor for PPD: in our study sixty-two percent of AR-PPD subjects had an anxiety disorder. There is an emerging literature describing the effects of anxiety on cortisol during pregnancy (Kane et al 2014; King et al 2010; O'Connor et al 2014) and in the postpartum (Labad et al 2011; Lord et al 2011) but substantial methodological variation among studies makes it difficult to identify clear associations. The study sample size did not allow us to examine potential differences in cortisol reactivity among the clinical phenotypes.…”
Section: Discussionmentioning
confidence: 99%